Analisis Kegiatan Ekstrakurikuler Pencak Silat Dalam Mengembangkan Nilai-Nilai Karakter Siswa Di SD Negeri Giriwangi - Devie Andrean Safitri; Agus Ahmad Wakih; Febri Fajar Pratama (Universitas 45 Surabaya, 2023)
The background of this research is the lack of development of good character values in the environment of Giriwangi State Elementary School. This research aims to find out and analyze the planning, implementation, and development of character values through extracurricular pencak silat activities. The method used in this research is Descriptive Qualitative Research, in accordance with Sugiono's opinion, this research is a research method based on the philosophy of postpositivism, which is used to research on natural object conditions, with data collection techniques in triangulation and research results emphasizing meaning rather than generalization. The subject of this study uses TGR movements and stances and at the end of the training students are tested on the material that has been learned. The results of the study state that as a result of Pencak Silat Extracurricular activities at SD Negeri Giriwangi, students can develop the main character values of PPK including Religion (Tolerance and honesty), Independence (Hard work), Gotongroyong (Cooperation and help), Nationalism (Love for the country), and Integrity (Social Care).